The prevalence of 3-hydroxy-3-methylglutaryl-Coenzyme a reductase variants in hypercholesterolaemic patients with statin intolerance - Phulukdaree, Alisa (University of Pretoria, 2025)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2024.